2017
DOI: 10.1080/13825585.2017.1397097
|View full text |Cite
|
Sign up to set email alerts
|

Same face, same place, different memory: manner of presentation modulates the associative deficit in older adults

Abstract: One of the more severe and consequential memory impairments experienced by older adults is the loss of the ability to form and remember associations. Although the associative deficit is often assumed to be unitary, memory episodes may contain different types of associations (e.g., item-item, item-context). Research in younger adults suggests that these different association types may involve different neural mechanisms. This raises the possibility that different association types are not equally affected by ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 22 publications
1
0
0
Order By: Relevance
“…The results highlight the strength of configural arrangements as part of the associative memory trace and the importance of maintaining configural congruency across memory phases as a means to bolster the transfer of associative information across phases in older adults. This finding is consistent with earlier behavioral work from our collaborative group (Overman, Dennis, McCormick-Huhn, Steinsiek, & Cesar, 2019; Overman et al, 2018) where we found that both the manner of encoding presentation as well as congruency of configural display was critical to memory success. Importantly, the current results suggest that the strength of this representation is preserved across the adult lifespan.…”
Section: General Conclusionsupporting
confidence: 92%
“…The results highlight the strength of configural arrangements as part of the associative memory trace and the importance of maintaining configural congruency across memory phases as a means to bolster the transfer of associative information across phases in older adults. This finding is consistent with earlier behavioral work from our collaborative group (Overman, Dennis, McCormick-Huhn, Steinsiek, & Cesar, 2019; Overman et al, 2018) where we found that both the manner of encoding presentation as well as congruency of configural display was critical to memory success. Importantly, the current results suggest that the strength of this representation is preserved across the adult lifespan.…”
Section: General Conclusionsupporting
confidence: 92%